Online Blood Banking System - Barka, Ali Ahmed (2010)
The importance of blood in the existence of human cannot be over emphasized. It supplies all nutrients and oxygen into the inner part of their body and body cells, and it has been medically proven that no one can survive without the presence of blood. Lack of access to blood has caused great havoc in the medical practice. The issue of blood bank, such as the way how the donated bloods are kept and how to access the blood are very critical for every hospital. In some cases the patient cannot get the blood at the right time due to the fact that the branches are not internetworked. Therefore, online blood banking is expected to solve the problem of inadequacy of blood when required for medical purposes. A prototype will be developed using the general design methodology.